(untitled) (Bioscience Journal, 2023)
The study analyzed the influence of temperature on the depth of cure of bulk-fill composite resins. Three discs (ISO 4049/2000) from each group were made, and four restorative materials were investigated: Opus Bulk-Fill Flow, Opus Bulk-Fill APS, Filtek™ One Bulk-Fill, and Filtek™ Bulk-Fill Flow. They were light-cured (Gnatus ± 1,200 mW/cm2) for 20 seconds, varying the temperature (23°C and 5°C) and simulating the use of the product both at room temperature and under refrigeration. The materials were inserted in aluminum matrices with 10 mm in depth and 4 mm in diameter. A clear film strip and a glass microscope slide were positioned at the top and bottom surfaces. The material was condensed and light-cured with the tip of the light source in close contact, for 20 seconds on the top surface. Immediately after irradiation, the samples were removed from the mold, and the uncured part was removed with a plastic spatula. The measurement was performed with a micrometer ± 0.1 mm, and the value was divided by 2. The data were analyzed with two-way ANOVA at a significance of 0.05. There was a statistical difference in the temperature between the results obtained in Opus Bulk-Fill APS (p <0.001) and Filtek™ Bulk-Fill Flow (p = 0.018) resins. For the temperature of 5°C, Filtek™ Bulk-Fill Flow showed a statistical difference compared to the other resins, while Opus Bulk-Fill Flow and Opus Bulk-Fill APS did not. For the temperature of 23°C, Filtek™ Bulk-Fill Flow maintained the statistical difference from the others, but Filtek™ One Bulk-Fill and Opus Bulk-Fill APS did not present statistical differences. Storing the Filtek™ Bulk-Fill Flow composite resin in the refrigerator caused a greater depth of cure than the other resins, and the depth of cure decreased at room temperature. As for Opus Bulk-Fill APS, the depth of cure decreased proportionally to the temperature decrease. The temperature may affect the depth of cure of some composite resins.